THE APPLICABILITY OF INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS (IPSAS) AND ITS IMPACT ON THE TRANSPARENCY OF GOVERNMENT FINANCIAL REPORTS: A SURVEY STUDY IN THE IRAQI ENVIRONMENT - Haider Layedh Meteab; Basim Mohammed Merhej; Ali Nadhem Abdulameer (International Journal of Business, Law and Political Science, 2025)
Objective: This study investigates the impact of adopting International Public Sector Accounting Standards (IPSAS) on enhancing the transparency of government financial reporting, with a particular focus on Iraq. The research problem stems from the gap between the growing demand for financial transparency and the challenges impeding IPSAS implementation, including legislative, technical, and human resource limitations. Method: Using a descriptive-analytical approach supported by a field survey of 200 respondents from government ministries, public institutions, and academia. Results: The study finds that IPSAS adoption significantly improves transparency, builds international trust, and strengthens anti-corruption measures through enhanced disclosure. Nevertheless, the results highlight persistent barriers such as weak technological infrastructure, insufficient professional expertise, and the need for substantial legislative reforms. Novelty: The study recommends updating accounting legislation, developing IT infrastructure, and implementing intensive training programs to ensure effective IPSAS adoption, thereby improving the quality of government financial reporting and fostering greater stakeholder trust at both local and international levels.